Bringing Depth to Education: Applying Existentialist Philosophy and its Implications in Developing Islamic Education - Rusdi, Rusdi (SYAMIL: Journal of Islamic Education, 2019)
Existentialism emphasizes the uniqueness of individuals and the importance of personal choice and responsibility. It encourages individuals to seek meaning and purpose in their lives, and to grapple with the difficult questions of existence. By applying existentialist philosophy to Islamic education, students can be empowered to take responsibility for their own learning and to engage with the deeper questions of life and spirituality. This paper examines the implications of applying existentialist philosophy to Islamic education, including the role of the teacher as a facilitator and guide rather than a strict authority figure, the importance of experiential learning and self-discovery, and the need to provide opportunities for students to explore and question their beliefs and values. The research method used in this study is literature review. This research will conduct a search and analysis of literature sources related to the application of existentialist philosophy in the development of Islamic education. The literature sources that will be used include books, scientific journals, articles, and official documents related to Islamic education and existentialist philosophy. The process of searching literature sources will be carried out using several online databases such as Google Scholar, JSTOR, ProQuest, and EBSCO. After the literature sources are found, the selection process will be carried out by identifying the relevance, credibility, and quality of the literature sources that will be used in this research. Research result, bringing depth to Islamic education through the application of existentialist philosophy can help students develop a stronger sense of identity, purpose, and meaning in their lives. It can also help students to better understand and appreciate the complexities and diversity of the Islamic tradition, and to engage with the world around them in a more meaningful and productive way.